Postoperative imaging of the multichannel cochlear implant. - Shpizner, B A; Holliday, R A; Roland, J T; Cohen, N L; Waltzman, S B; Shapiro, W H (American Journal of Neuroradiology, 1995)
PURPOSE To present the postoperative radiographic appearance of the multichannel cochlear implant and to suggest criteria for the radiographic evaluation of postimplant patients. METHODS One hundred forty-one patients, 73 female and 68 male, had multichannel cochlear implants inserted. One hundred thirty-five intraoperative radiographs, 31 postoperative radiographic examinations, and 10 postoperative CT examinations were retrospectively reviewed. RESULTS In 135 patients, a Stenver's or anteroposterior projection confirmed the normal placement of the implant by demonstrating the electrodes to be regularly spaced and gently curved within the first turn of the cochlea. The insertion depth was determined by counting the number of electrodes that projected medial to the cochlear promontory. In 5 patients in whom intracochlear placement of the electrode array could not be confirmed on plain radiographs, CT demonstrated the location of the electrode array. In 3 patients with postoperative infections, CT either correctly identified or excluded the presence of a collection beneath the implant. CONCLUSION Plain radiographs of the temporal bone are sufficient for the postoperative treatment of the majority of postimplant patients. CT should be performed when plain radiographs cannot adequately show the location of the electrode array or if postoperative infection is suspected.